Application of Polyoxometalate-based composites for sensor systems: A review - Khalilpour, Hamid; Shafiee, Parisa; Darbandi, Amirhossein; Yusuf, Mohammad; Mahmoudi, Shirin; Moazzami Goudarzi, Zahra; Mirzamohammadi, Sadegh (Journal of Composites and Compounds, 2021)
Composites based on polyoxometalates (POMs) have been increasingly attracted by many researchers due to their multitudinous architectures and excellent redox activities as well as outstanding proton and electron transport capacities. Lately, much research has been done on POMs composited with well-porous framework materials (including ZIFs, MOFs) or conducting polymers, carbon quantum dot (CQD), graphene, carbon structures (e.g. carbon nanotubes (CNTs)), and metal nanoparticles (NPs). The results exhibited improved stability and enhanced electrochemical performances. Hence, developing POMs and POM-based composite materials (PCMs) has long been a topic of interest for chemical researchers. Herein, the properties and applications of pristine POMs, doped POMs, and composite-based POMs are reviewed in detail. The various compositions of POMs with sensing application such as POMs-nanocarbon composites (POMs-graphene composites and POMs-carbon nanotube composites), POMs-conductive polymer composites, and POMs-metal composites are also investigated in this review.